Never mind the bug: no differences in infection-free survival after periprosthetic joint infections with Staphylococcus aureus, Coagulase-negative Staphylococcus, or Streptococcus - Brüggemann, Anders; Hailer, Nils P. (Frontiers in Microbiology, 2025)
BackgroundPeriprosthetic joint infection (PJI) is a devastating complication following arthroplasty of the hip or knee joint and can be challenging to treat, depending on the underlying pathogen. There is still a debate whether streptococcal PJI are more difficult to treat than those caused by staphylococci. We aimed to investigate if the treatment results after PJI caused by Staphylococci aureus (S. aureus), Coagulase-negative Staphylococci spp. (CoNS) or Streptococci differ.Patients and methodsThis study was designed as a retrospective observational study on patients with PJI caused by either streptococci or staphylococci in the hip or knee treated at a tertiary referral center between 1998 and 2021. Patients were identified in the local PJI register and data were collected by medical chart review performed minimum 1 year after the index PJI. Patients with polymicrobial infections or incomplete data were excluded, leaving 299 patients with streptococcal or staphylococcal PJI for final analysis. These patients were categorized according to the underlying pathogen: 114 were S. aureus 121 were CoNS, and 64 Streptococci. Infection-free survival was defined as the absence of (1) further surgery to the index joint due to PJI, (2) suppressive antibiotic therapy, and (3) death due to PJI and was assessed using the Kaplan–Meier method. Cox regression models were fitted to estimate the risk of infection relapse adjusted for relevant confounders.ResultsWe found no statistically or clinically significant difference in unadjusted survival between the three groups. Infection-free survival at 2 years was 71% (95%CI: 63–80) for S. aureus, 75% (95%CI: 67–84) for CoNS, and 60% (95%CI: 60–84) for Streptococci. The adjusted hazard ratios (HR) for the risk of infection relapse with S. aureus as the reference were 1.2 (95%CI: 0.7–2.0) for CoNS and 1.1 (95%CI: 0.6–2.0) for Streptococci. For all three groups of bacteria, survival was lower when DAIR was performed in comparison to exchange surgery.DiscussionIn our cohort, there was no difference in infection-free survival between the three groups. Albeit limitations due to the study design, it seems that streptococcal PJI do not have to be considered more difficult to treat than their staphylococcal counterparts. Exchange surgery shows favorable results in all groups compared to DAIR.